Point-of-Care Diagnostic Assays and Novel Preclinical Technologies for Hemostasis and Thrombosis - Caruso, Christina; Lam, Wilbur A. (Seminars in Thrombosis and Hemostasis, 2021)
Hemostasis is a complex wound-healing process involving numerous mechanical and biochemical mechanisms and influenced by many factors including platelets, coagulation factors, and endothelial components. Slight alterations in these mechanisms can lead to either prothrombotic or bleeding consequences, and such hemostatic imbalances can lead to significant clinical consequences with resultant morbidity and mortality. An ideal hemostasis assay would not only address all the unique processes involved in clot formation and resolution but also take place under flow conditions to account for endothelial involvement. Global assays do exist; however, these assays are not flow based. Flow-based assays have been limited secondary to their large blood volume requirements and low throughput, limiting potential clinical applications. Microfluidic-based assays address the aforementioned limitations of both global and flow-based assays by utilizing standardized devices that require low blood volumes, offer reproducible analysis, and have functionality under a range of shear stresses and flow conditions. While still largely confined to the preclinical space, here we aim to discuss these novel technologies and potential clinical implications, particularly in comparison to the current, commercially available point-of-care assays.
Keywords: hemostasis; platelet function; coagulation assays; point-of-care testing; microfluidics